Muslim Students' Understanding about Interconnection of Gravity in Science and The Qur'an - Kamila Amalia; Suliyanah Suliyanah (Indonesia Approach Education, 2020)
Gravity is known as a discovery made by Sir Isaac Newton. Long before this theory was put forward, the Qur'an came down first, and some verses indicated the existence of gravity, but not everyone understood these signs. There are still many Islamic schools in Indonesia that have not yet studied science by relating the Qur'an. This study aims to determine the extent of Muslim students' understanding and to find out what Muslim students think about gravitational interconnection in science and the Qur'an. This research used descriptive qualitative research methods. The research data were obtained from interviews and questionnaires. Participants in this study were fifty participants, namely students from the Al-Amin Islamic Boarding School, Mojokerto, East Java. The results of this study indicate that the majority of students have a good understanding of Newton's gravitational interconnection in Science and the Qur'an. Most of the respondents argue that Newton's idea of ​​gravity is related to the verses of the Qur'an, especially QS Al-Hajj 22:65, QS Al-Mursalat 77:25, QS Maryam 16:25, and QS Al-Qori'ah verses 1-5. This research can make Muslim students improve their understanding of gravity in science and the Qur'an and also increase their piety to God.